SISTEM INFORMASI PENGOLAHAN ZAKAT DAN INFAQ PADA MASJID AGUNG PALEMBANG - Andrian Novansyah; Hastha Sunardi; Mustafa Ramadhan (UNIVERSITAS INDO GLOBAL MANDIRI)
Zakat is a certain amount of assets that must be issued by a person who is Muslim and given to groups who deserve it (the poor, ibn sabil, fisabilillah and so on). Processing zakat includes implementation, collection and distribution of zakat. Processing Zakat and Infaq in Palembang Grand Mosque has a system for recording and distribution of zakat funds and infaq which still has the disadvantage that the recording system is still using the manual method that allows the loss or corruption of data, the registration process is slow to make the queue is getting and the process of distributing zakat increasingly delayed and slow report generation. Therefore, researchers propose Processing Information Systems Zakat and Infaq that can overcome the problems found in the previous system, enabling the recording, processing and printing of data is done quickly, precisely. Development of systems using the Waterfall method as the flow of system development. By creating a Data Flow Diagrams (DFD), Flowchart, Data Dictionary, Entity Relationship Diagram (ERD), Data Normalization, File Specifications, Process Specifications, Chart Structured as a tool in the analysis and design. The programming language used Visual Basic 6.0 and Microsoft Access 2007 as the database. These systems process data muzakki, mustahiq, infaq, operating expenses, zakat fitrah, zakat maal, zakat income, the distribution of zakat, reports. With applicable Zakat Processing Information Systems and Infaq expected to facilitate the processing of zakat and infaq.